TETANUS OUTBREAK IN AN ORGANIZED GOAT FARM IN CAUVERY DELTA ZONE, TAMILNADU: DIAGNOSIS AND THERAPEUTIC MANAGEMENT - Puvarajan, B; Lurthu, T Reetha; Manickam, R (International Journal of Allied Sciences (IJAS), 2022)
Outbreaks of tetanus, a sporadic disease caused by pathogenic C.tetani spores and toxins, have mostly been reported in sheep. This study, however, investigates a tetanus outbreak among goats at a private farm in Adhirampattinam block, Thanjavur district. The affected goats had recently undergone ear tagging for identification and insurance. Ten goats exhibited ear-region wounds, suggesting scab formation and potential C.tetani infection. Clinical examinations revealed symptoms indicative of C.tetani infection, while anerobic culture of ear swabs and scabs confirmed the presence of Gram-positive bacilli with terminal spores. Contaminated ear-tagging instruments were the likely cause. Strepto-penicillin treatment for 3-5 days at 2.5g/day effectively reduced fatalities. The study proposes that wound exudation could facilitate an anaerobic environment for C.tetani spore germination and toxin production. Vaccination and strict hygienic practices were advised, especially during kidding season before monsoon onset